Best Practices: Securing Your Firm from Cyberattacks. - MILLER, NATHAN (Architect, 2018)
The article offers suggestions for securing the architecture firm from cyberattacks with connected to Internet of Things (loT) networks, with building management systems and building information modelling (BIM) software. Topics discussed include report regarding hacking-related breaches, standard regarding cybersecurity with storage of controlled unclassified information and future of cryptocurrencies like Bitcoin in architecture and construction.